Perspectives of residential aged care facilities' staff on the identification and recording of residents' medication‐related goals of care. (9th August 2019) - Sawan, Mouna; Kouladjian O'Donnell, Lisa; Hilmer, Sarah N.
Abstract: Objective: This study primarily aims to explore residential aged care facility (RACF) staff views on the utility of a computerised clinical decision support system (CCDSS) that incorporates validated goal‐directed deprescribing tools and guides to identify residents' goals for medications. Methods: A qualitative study was conducted in four RACFs. Semi‐structured interviews or focus groups were conducted with 19 participants, representing various types of clinical and care staff. Results: According to staff, the use of a CCDSS was useful as it facilitated resident (including people with dementia), and caregiver engagement to obtain comprehensive information about the residents' goals and medication concerns. Staff perceptions of the increased workload and that some residents and caregivers would have limited involvement in discussions were barriers to the adoption of a CCDSS. Conclusion: Integration of a CCDSS into practice, accompanied with staff training and education, has the potential to improve goal‐directed pharmaceutical care.